2020
DOI: 10.1111/jocn.15358
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge, attitudes, and behaviours related to pressure injury prevention: A large‐scale cross‐sectional survey in mainland China

Abstract: Aims and objectives To determine the level of and factors in nurses’ knowledge, attitudes and behaviours towards pressure injury (PI) prevention. Background Although there has been a declining trend in global PI prevalence and hospital‐acquired rates in recent years, this has not been the case in China. Evidence in the literature indicates the importance of nurses' knowledge, attitudes and behaviours for promoting PI prevention. Design Cross‐sectional study. Methods A total of 1,806 nurses from 10 tertiary gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 37 publications
10
70
4
4
Order By: Relevance
“…The results in the (Table 4.3) revealed that there is a significant association between the levels of education with nursing staffs' knowledge in the study sample related to main domain toward prevention of PU at post-test. This finding could be supported through study conducted by (29) in China; the researcher reported that the highest educational group (bachelor or higher) was found to have an association of significance with regard to their knowledge, which concordant with the current study.…”
Section: )supporting
confidence: 89%
“…The results in the (Table 4.3) revealed that there is a significant association between the levels of education with nursing staffs' knowledge in the study sample related to main domain toward prevention of PU at post-test. This finding could be supported through study conducted by (29) in China; the researcher reported that the highest educational group (bachelor or higher) was found to have an association of significance with regard to their knowledge, which concordant with the current study.…”
Section: )supporting
confidence: 89%
“…The present study revealed that 33.1% of participants had not received training on PI prevention over the last year, which might have been due to nurses' heavy workloads and lack of time to participate in training programs. Nursing managers should take note of this issue and establish strategies to increase ICU nurses' participation in PI training programs so as to improve their PI prevention 31 This large discrepancy might be due to the different questionnaires and cutoff scores between that study and the current one. The earlier study applied the Pressure Ulcer Knowledge Test (PUKT).…”
Section: Icu Nurses' Knowledge Of Pi Preventionmentioning
confidence: 84%
“…34 In this study, we translated total scores into percentage scores and set mean cutoff score at 80/100 to reflect sufficient knowledge of PI prevention on the part of the ICU nurse, in accordance with a similar study conducted among Chinese general nurses. 31 Participants' PI prevention attitude was measured by the Attitude toward Pressure Ulcer Prevention Instrument (APuP), developed and validated by Beeckman et al 35 The instrument consists of 13 items covering five themes:…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations